Anthropogenic disturbance favours generalist over specialist parasites in bird communities: Implications for risk of disease emergence. (13th June 2021) - Dharmarajan, Guha; Gupta, Pooja; Vishnudas, C. K.; Robin, V. V.
Abstract: Niche theory predicts specialists which will be more sensitive to environmental perturbation compared to generalists, a hypothesis receiving broad support in free‐living species. Based on their niche breadth, parasites can also be classified as specialists and generalists, with specialists infecting only a few and generalists a diverse array of host species. Here, using avian haemosporidian parasites infecting wild bird populations inhabiting the Western Ghats, India as a model system, we elucidate how climate, habitat and human disturbance affects parasite prevalence both directly and indirectly via their effects on host diversity. Our data demonstrate that anthropogenic disturbance acts to reduce the prevalence of specialist parasite lineages, while increasing that of generalist lineages. Thus, as in free‐living species, disturbance favours parasite communities dominated by generalist versus specialist species. Because generalist parasites are more likely to cause emerging infectious diseases, such biotic homogenisation of parasite communities could increase disease emergence risk in the Anthropocene. Abstract : The Anthropocene has been characterised by human‐mediated environmental modifications, such as deforestation and urbanisation. Here, we show that human‐mediated disturbance can favour parasite communities dominated by generalist versus specialist species. Because generalist parasites are more likely to cause emerging infectious diseases, such biotic homogenisation of parasite communities could increase risk of disease emergence in the Anthropocene.